Sociocultural Competence of Schoolchildren: to the Problem of Use of Means of its Realization at the Lessons of Ukrainian - Koryts’ka, Halyna (Pedagogical Discourse, 2012)
The growing of the role of sociocultural competence of students at the modern development stage of education has been grounded in the article. The means of its implementation at the Ukrainian language lessons has been considered.